FUNCTIONALIZATION OF ISLAMIC PHILOSOPHICAL THOUGHT - Natsir, Muhammad Miftahul (HUNAFA Jurnal Studia Islamika, 2024)
The study of the functionalization of Islamic philosophical thought tends to be very important to be studied more deeply because the study never stops to be debated. The purpose of this paper is to understand 3 things: First, the paradigm of the functionalization of Islamic philosophical thought Second, the internal and external factors that influence it Third, the positive and negative implications for Muslims The method used by the researchch library with the library text approach is based on the Zed Mestika theory as for data collection by means of literature study and analyzed by content analysis techniques . The results found are 3 things: First, the paradigm of functionalization of Islamic philosophical thought has 3 forms: (1) Answering the challenges of the times (2) Approaching Islamic education (3) Understanding the text of the Qur'an. Second, internally there are 3 factors that affect it: (1) Religious Commandments (2) Islamic traditions (3) the spirit of Muslims seeking the truth. Externally, there are 3 factors: (1) The influence of Greek philosophy, (2) The demands of the times, (3) The challenge of postmodernism. Third, the positive implications for Muslims are 3 things: (1) Understanding the essence of oneself 2) Fostering a moderation attitude (3) The development of Islamic education. Meanwhile, the negative implications are 3 things: (1) Conflict of Muslims (2) Accusations against Imam Al-Ghazali covering ijtihad (3) Mixed with distorted thinking The conclusion that this paper shows that the functionalization of Islamic philosophy is very effective in contributing to the thinking of Muslims.